Impact of glyphosate on the rhizosphere microbial communities of a double-transgenic maize line D105 - Wang, Guihua; Yang, Shuqian; Feng, Shilin; Zhao, Guofen; He, Xiaoyong; Han, Xiaodong (Frontiers in Sustainable Food Systems, 2024)
Plant roots shape the rhizosphere microbiome, recruiting microbes with beneficial functions. While genetically engineered crops offer yield advantages, their impacts on rhizosphere microbial communities remain understudied. This study evaluated the effects of transgenic maize, alongside a non-transgenic counterpart, on rhizosphere bacterial and fungal community composition using 16S rRNA and ITS amplicon sequencing. Additionally, glyphosate was used to evaluate its impact on microbial assembly and the magnitude of its effect at various maize growth stages. The results showed that transgenic maize D105 line significantly increased bacterial alpha diversity but not fungal diversity. Beta diversity analysis showed clear separation between bacterial and fungal communities at higher glyphosate treatment. Specific bacterial taxa such as Pseudomonas and Sphingomonas were enriched, while fungal taxa such as Ascomycota, Lasiosphaeriaceae, Verticillium were differentially abundant in glyphosate treatments. LEfSe analysis identified distinct enrichment patterns of bacterial (Proteobacteria and Actinobacteria) and fungal taxa (Verticillium and Guehomyces) associated with the transgenic line and glyphosate levels. KEGG functional analysis suggested potential impacts on bacterial metabolic pathways and shifts in fungal trophic modes (saprotrophs, pathogens) within the rhizosphere microbiome. This research provides insights into the classification, functional relationships, and underlying mechanisms shaping microbial communities carrying insect resistance and glyphosate resistance traits.